👤

VĂ ROG SĂ MĂ AJUTAȚI LA ACEST EXERCIȚIU:
[tex] \frac{7}{\sqrt{11}-2} - \frac{2}{\sqrt{11}-3} [/tex]
DAU CORONIȚA!!!!!


Răspuns :

prima ecuatie se amplifica cu V11+2 si a doua cu V11+3
7(V11+2)/(11-4)-2(V11+3)/(11-9)=7(V11+2)/7-2(V11+3)/2=       V11+2-V11-3= -1

Se foloseste relatia (a+b)(a-b)=a^2-b^2

Evee
[tex] \frac{7}{ \sqrt{11} -2} - \frac{2}{ \sqrt{11}-3} = \frac{7( \sqrt{11} +2)}{ \sqrt{11 ^{2} -2 ^{2} } } - \frac{2( \sqrt{11} +3)}{ \sqrt{11 ^{2} }- 3^{2} } = \frac{7 \sqrt{11}+14 }{11-4} - \frac{ 2\sqrt{11}+6 }{11-9} = [/tex]=
=[tex] \frac{7 \sqrt{11}+14 }{7} - \frac{2 \sqrt{11}+6}{2} = \frac{2(7 \sqrt{11}+14 ) }{14}-\frac{7(2 \sqrt{11}+6)}{14} = \frac{14 \sqrt{11}+28 }{14} - \frac{14 \sqrt{11} +42}{14} = [/tex]=[tex]- \frac{14}{14} =-1[/tex]